The Symbolic Meaning Study of Java's Panggih Wedding Traditions in Surakarta - Yustina Denik Risyanti; Bonaventura Ngarawula; Junianto Junianto; Ray Octafian (Journal of Social Science, 2022)
Javanese Surakarta wedding customs are a cultural heritage sourced from the palace, with unique procedures. Each stage has a special mechanism that contains values ​​and meanings as a guide when the couple builds a family. This qualitative study with a phenomenological approach aims to reveal the symbolic meaning of the Panggih ceremony in Javanese Surakarta wedding customs in the Surakarta City environment. This qualitative reseach collecting data with participant observation techniques and in-depth interviews obtained from research subjects. Data analysis uses an interactive model. Data analysis is carried out interactively and continuously until complete data is obtained. The informants in this study were two people who lived in Surakarta City by profession as senior make-up artists, both of whom had long-handled the procedures for Javanese Javanese wedding ceremonies in Surakarta. The results of the study found that in the Panggih ritual, Javanese Surakarta wedding customs were included in the core series, which was carried out full of sacredness under the order, before starting with the stage of handing over the banana sanggan, nebus Mayang twins, followed by the main stages consisting of Balangan suruh, and ngidak then. This research is different from previous research. This study examines the reality of the Panggih ceremony, specifically by the rules according to the standard. The conclusion is based on the findings in the field that the Panggih ritual is a core stage carried out according to the rules. Each stage contains symbols with meaningful values ​​as guidelines for couples getting married.